Media as Platforms of Da'wah among Muslim Converts in Borneo - Salinayanti, Salim (Universiti Sultan Zainal Abidin, 2020)
The study examined the use of media as tools of Muslim converts’ da’wah in Sabah, Sarawak and Brunei. There were two categories of media used in this study; social media (Facebook, YouTube, website, blog) and traditional media (television, radio, book, newspaper). The study interviewed 42 informants who lived in the city areas of Sabah, Sarawak and Brunei. The data obtained was arranged into themes and evaluated using descriptive and interpretive analysis approach. The study revealed that most informants partook in disseminating da’wah in media, primarily social media. The informants mostly ‘share’ the posts of others such as famous quotes and the videos of preachers. There were different levels of frequency of the informants’ posts on social media ranging from always to seldom. A few informants however, refrained from using media as platforms to disseminate da’wah because they did not want to offend their non-Muslim ‘friends’ on Facebook, and also they believed they did not have sufficient knowledge to disseminate da’wah.